2004
DOI: 10.1016/j.intcom.2003.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of young children regarding interface layouts in child community web sites

Abstract: This study investigates the child preferences regarding interface layouts in child community web sites. The objective of studying this area is to identify ways of making web sites more usable for children. Two experiments are conducted: interface layout experiment and layout evaluation. In the interface layout experiment, researchers recruited eight fifth-grade students with approximately oneyear of Internet experience to arrange interface components and make research interfaces. During the layout evaluation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Web page developers frequently arrange on-screen interfaces based on subjective perceptions or functional website requirements [22].…”
Section: ) Layout and Modulesmentioning
confidence: 99%
“…Web page developers frequently arrange on-screen interfaces based on subjective perceptions or functional website requirements [22].…”
Section: ) Layout and Modulesmentioning
confidence: 99%
“…For example, Lewis et al [190] reported on the use of walkthroughs to elicit designs for software where children could explore the creation of scientific models. Chen et al [48] worked with ten and eleven-year old children to develop web-based user interfaces to community websites. The children were asked to develop layouts for the web pages.…”
Section: Designmentioning
confidence: 99%
“…Therefore, when considering the use of PDAs in vocabulary learning applications, it is important to evaluate whether or not young users have a particular preference for the PDA format, and hence for the orientation of its screen. Chen [4] investigated the preferences of young children for interface layouts in child-orientated web sites and pointed out that children have immature cognition abilities. Therefore, the interface design is of particular importance in childorientated applications.…”
Section: Interface Orientationmentioning
confidence: 99%
“…Chen [4] examined users' satisfaction with various menus and interface layouts by requesting them to perform certain tasks and to then use a short questionnaire to evaluate their degree of satisfaction. In the present study, 30 participants were individually shown each of the four design samples in a random sequence.…”
Section: Evaluation Of Nested Designsmentioning
confidence: 99%